Adaptation of Lactobacillus casei Zhang to Gentamycin Involves an Alkaline Shock Protein - Zhang, Wenyi; Guo, Huiling; Cao, Chenxia; Li, Lina; Kwok, Lai-Yu; Zhang, Heping; Sun, Zhihong (Frontiers in Microbiology, 2017)
Lactobacillus (L.) casei Zhang is a koumiss-originated probiotic strain, which was used as a model in a long-term antibiotics-driven evolution experiment to reveal bacterial evolutionary dynamics; and we isolated gentamycin-resistant L. casei Zhang descendents. To decipher the gentamycin resistance mechanism, here we cultivated the parental L. casei Zhang and its descendent cells in an antibiotics-containing environment to compare their global protein expression profiles using the iTRAQ-based proteomic approach. A total of 72 proteins were significantly up-regulated (>2.0 fold, P<0.05), whilst 32 proteins were significantly down-regulated <-2.0 fold, P<0.05) in the descendent line. The gentamycin-resistant descendent line showed elevated expression in some carbohydrates, amino acids, and purine metabolic pathways. Several stress-related proteins were also differentially expressed. Among them, one alkaline shock protein, asp23, was up-regulated most in the gentamycin-resistant strain (21.9-fold increase compared with the parental strain). The asp23 gene disruption mutant was significantly more sensitive to gentamycin compared with the wild type, suggesting an important role of this gene in developing the gentamycin-resistant phenotype in L. casei. Our report has described the adaptation of a probiotic strain that has acquired antibiotics resistance through long-term antibiotics exposure at the proteome level, and we revealed a novel mechanism of gentamycin resistance.